The application of IoT in entrepreneurial activities: moving towards a sustainable and resilient business - Mohd Radzi, Naziatul Aziah; Saidi, Normaizatul Akma; Saidin, Siti Salina (Universiti Teknologi MARA, Terengganu, 2022)
We may not find the slogan “everything at your fingertips” strange. The current pattern of modernization and the advancement of technology have led to the majority of the country’s population owning electronic devices. Furthermore, the majority of urban and rural areas now have improved Internet network access. Consequently, the Internet of Things (IoT) is not a new concept, and we are now aware that we are moving in its direction. The COVID-19 pandemic has demonstrated the importance of the Internet of Things (IoT) during difficult times, especially when movement control orders (MCOs) have been implemented to curb the spread of the pandemic.